2019
DOI: 10.1016/j.patcog.2019.05.016
|View full text |Cite
|
Sign up to set email alerts
|

Making the dynamic time warping distance warping-invariant

Abstract: The literature postulates that the dynamic time warping (dtw) distance can cope with temporal variations but stores and processes time series in a form as if the dtw-distance cannot cope with such variations. To address this inconsistency, we first show that the dtw-distance is not warping-invariant. The lack of warping-invariance contributes to the inconsistency mentioned above and to a strange behavior. To eliminate these peculiarities, we convert the dtw-distance to a warping-invariant semi-metric, called t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…where P a i is the coordinate sequence that starts at the i th vertex in A. Subsequently, the canonical warping distance between the sequences in CodeSet a and P b , denoted as the minimum, serves as the ultimate distance between A and B, as depicted by Equation (7).…”
Section: 𝐽 (π‘Š π‘Š 𝑉 𝑉 ) = 𝑉 π‘‹π‘Š βˆ’ 𝑉 π‘Œπ‘Šmentioning
confidence: 99%
See 1 more Smart Citation
“…where P a i is the coordinate sequence that starts at the i th vertex in A. Subsequently, the canonical warping distance between the sequences in CodeSet a and P b , denoted as the minimum, serves as the ultimate distance between A and B, as depicted by Equation (7).…”
Section: 𝐽 (π‘Š π‘Š 𝑉 𝑉 ) = 𝑉 π‘‹π‘Š βˆ’ 𝑉 π‘Œπ‘Šmentioning
confidence: 99%
“…Pattern recognition, a cornerstone of computer vision, has seen various methodologies proposed, including Dynamic Programming (DP), Dynamic Time Warping (DTW), and Canonical Time Warping (CTW) [6][7][8]. DP techniques leverage contour point sequences to establish local correspondences between shapes for measuring shape dissimilarity.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, the required computation time and storage of TWI-distance sometimes were less than the DTW-distance. They suggested that the proposed TWI-distance was a more efficient and consistent option [26].…”
Section: Breakdown Of the Empirical Mode Decomposition (Emd) And Dynamentioning
confidence: 99%
“…Specifically, SAX ignores the pattern of a shift in the value of the segment, which in some cases can lead to an incorrect classification, because it is not capable of distinguishing different time series with different patterns from the same average value symbol. Dynamic Time Warping (DTW) [15], [16] is used to calculate the value change trend in the passenger flow segment, the value change trend during each passenger flow data segment is further calculated using SAX, and a new weight equivalent distance is created taking into account the mean value and trend information of the passenger flow data.…”
Section: Introductionmentioning
confidence: 99%